The Educational Thought of KH. Hasyim Asy’ari: A Study of the Book Adabul 'Alim wal Muta'allim - Syarifah, Syarifah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2025)
This study aims to explore the educational thought of KH. Hasyim Asy’ari as presented in his book Adabul ‘Alim wal Muta’allim, focusing on the fundamental educational concepts developed within the work and their relevance to contemporary Islamic education. The research employs a library research approach, where data is gathered from primary texts related to KH. Hasyim Asy’ari’s thought and relevant literature. Descriptive-qualitative analysis is used to uncover the educational values contained in the book and to examine their application in the modern educational context. The findings reveal that KH. Hasyim Asy’ari emphasized the importance of adab (etiquette), sincere intention, and respect for teachers as the main pillars of the educational process. His thoughts integrate both intellectual and moral aspects, with the goal of forming individuals who are knowledgeable and morally upright. Additionally, the educational values in Adabul ‘Alim wal Muta’allim are highly relevant to the challenges of contemporary education, especially in strengthening character and shaping the morals of students. The study also shows that KH. Hasyim Asy’ari’s ideas make a significant contribution to the development of Islamic education curricula, emphasizing the integration of knowledge and ethics in teaching and learning. This research contributes to a deeper understanding of traditional Islamic education and its relevance in modern educational contexts. The findings provide a basis for developing a more holistic educational model rooted in spiritual and moral values.